1977
DOI: 10.1111/j.1365-3059.1977.tb01025.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Banker’ Plant Production of Encarsia formosa Gahan and its Use in the Control of Glasshouse Whitefly on Tomatoes

Abstract: SUMMARY ‘Banker’ plants on which a whitefly/parasite interaction had been well established successfully controlled glasshouse whitefly (Trialeurodes vaporariorum (Westw.)) when introduced on to a commercial tomato crop at rates of 89 or 50 plants per hectare. Each plant produced about 8000 parasites over a minimum period of eight weeks and the presence of whiteflies and honeydew on these plants provided the adult parasites with a source of food during the early stages of the infestation. The principal advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 2 publications
0
22
0
1
Order By: Relevance
“…obs.). In addition, by choosing a banker plant of the same plant species as the crop, need for additional propagation of specific banker plants is avoided and banker plants may be harvested alongside the crop (Stacey, 1977). In fact, Goolsby and Ciomperlik (1999) showed that their cantaloupe banker plants produced a normal yield, thus offsetting the cost of banker plants.…”
Section: B the Banker Plantmentioning
confidence: 97%
See 1 more Smart Citation
“…obs.). In addition, by choosing a banker plant of the same plant species as the crop, need for additional propagation of specific banker plants is avoided and banker plants may be harvested alongside the crop (Stacey, 1977). In fact, Goolsby and Ciomperlik (1999) showed that their cantaloupe banker plants produced a normal yield, thus offsetting the cost of banker plants.…”
Section: B the Banker Plantmentioning
confidence: 97%
“…In a few cases, among the investigated systems (6% of systems listed in Tables 2-4), the plant species chosen as banker plant is the same as the crop species (Parr and Stacey, 1976;Stacey, 1977;Goolsby and Ciomperlik, 1999;Pickett et al, 2004;G. Murphy, pers.…”
Section: B the Banker Plantmentioning
confidence: 99%
“…have proposed using the term ''banker plants'' to describe this strategy. The same term was first coined by Stacey (1977) to describe greenhouse produced tomato plants inoculated with parasitoids. He recognized that parasitoids introduced into greenhouses on the same plants used for propagation could reduce the cost of control over repeated releases during the growing season.…”
Section: Introductionmentioning
confidence: 98%
“…BPs are non-crop plants that provide resources to sustain natural enemies of pests in the absence of their prey (Stacey, 1977;Frank, 2010;Huang et al, 2011;Parolin et al, 2012 a, b). They are introduced as rearing systems for biocontrol agents.…”
Section: Introductionmentioning
confidence: 99%